2013
DOI: 10.3109/0142159x.2013.801940
|View full text |Cite
|
Sign up to set email alerts
|

Exploring medical student decisions regarding attending live lectures and using recorded lectures

Abstract: Lectures, both live and recorded, are important for student learning. Decisions about lecture placement in the curriculum need to be based on course content and lecturer quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 12 publications
7
79
1
3
Order By: Relevance
“…35,10,12–14 We also included research related to medical student learning preferences and behavior in undergraduate courses. 1517 After reviewing the range of opinions related to learning kidney physiology, we identified five major domains: the student’s comprehension of kidney physiology, learning preferences, course characteristics, perceived clinical relevance of kidney physiology, and perception of nephrology as a career. The primary researcher (J.K.R.)…”
Section: Definition Of the Statement Setmentioning
confidence: 99%
“…35,10,12–14 We also included research related to medical student learning preferences and behavior in undergraduate courses. 1517 After reviewing the range of opinions related to learning kidney physiology, we identified five major domains: the student’s comprehension of kidney physiology, learning preferences, course characteristics, perceived clinical relevance of kidney physiology, and perception of nephrology as a career. The primary researcher (J.K.R.)…”
Section: Definition Of the Statement Setmentioning
confidence: 99%
“…Releasing recordings after the class session has logistical advantages and disadvantages, but it is difficult to assess how allowing students access to recorded lectures affects learning. While students favor recorded lectures for a variety of reasons, 11 this preference does not always align with the most educationally beneficial results. Thus, the goal of this study is to better understand how recorded lectures may influence the learning process.…”
Section: A J P E a C C E P T E D D R A F Tmentioning
confidence: 99%
“…10,11 Pharmacy and other health profession D r a f t schools often integrate new technologies into the classroom and one of these technologies has been lecture capture. Lecture capture allows professors to record a class and make that recording available to students after the class session has concluded.…”
Section: A J P E a C C E P T E D D R A F Tmentioning
confidence: 99%
“…Many studies have found that students do not tend to replace attendance at face to face lectures with ilectures (Gorissen, Van Bruggen, & Jochems, 2012;Gupta & Saks, 2013;Karnad, 2013;Larkin, 2010;Mather, Caesar, Chin, & Fei, 2015) but instead prefer a blended learning approach where they mix a little of both modes together (e.g., Zeldenryk & Bradey, 2013). A study conducted by Saunders and Hutt (2015) in a British university revealed that only 10% of the participants (n=84) resorted to ilectures as a substitute for face-to-face instruction.…”
Section: Introductionmentioning
confidence: 99%